Menjadi Muslim di Negara Multikultural: Dinamika, Tantangan dan Strategi dalam Perspektif Fikih Multikultural - Tahir, Masnun (Universitas Islam Negeri Raden Intan Lampung, 2017)
Indonesian Islam is a unique one, pluralist and multiculturalist as Nahdlatul Ulama Islam, Muhammadiyah Islam, Shiah Islam, Sunni Islam and much more which has diverse consequences for its followers. As matter of fact, the diversity continues to face challenges. An Accusation against moderate and multiculturalism through violence is perpetrated by individual actors, mass organization and the most authoritatve institution that should be the guarantor of religious moderatism within the framework of Indonesian-ness. At the extreme level, the resistance is manifested in a series of intolerant actions such as expulsion.This paper aimed to present how life strategy in the nuances of multicultural from the perspective of Islamic law. The idea of fiqh that is sensitive to multiculturalism becomes important for Muslims in Indonesia to have a diversity of perspectives in the daily basis.